Dějinný původ určení člověka jako ,,rozumného živočicha" - Benyovszky, Ladislav (Lidé města, 2000)
The presented reflection is methodologically based on Heidegger´s distinction of the "historical examination" (historische Beobachtung) and "historical entry to the sphere of sense" (geschichtliche Besinnung). In the context of this distinction the historical (geschichtliche) origin examines the man as a reasonable creature. This means that it shows in which way the relationship between man and the world (Ereignis) must "occur" if it is to be mortal (Sterbliche) - the basic definition of the human kind from the viewpoint of the thought. It must be dealt with only as a living being endowed with the word or reason (ZOON LOGON ECHON, animal rationale). This definition of the human kind, which is basic and original for classical philosophical studies, specifies the reflection through its primitive forms, Aristotle's and Plato's definition of the soul.